Neutrophils rapidly transit inflamed lymphatic vessel endothelium via integrin‐dependent proteolysis and lipoxin‐induced junctional retraction. Issue 6 (27th July 2015) - Rigby, David A.; Ferguson, David J. P.; Johnson, Louise A.; Jackson, David G.
Abstract : Adhesion of neutrophils to inflamed lymphatic endothelium via β2 integrin triggers protease and lipoxin activities promoting junctional retraction and rapid transmigration. Abstract : Neutrophils are the first leukocyte population to be recruited from the circulation following tissue injury or infection, where they play key roles in host defense. However, recent evidence indicates recruited neutrophils can also enter lymph and shape adaptive immune responses downstream in draining lymph nodes. At present, the cellular mechanisms regulating neutrophil entry to lymphatic vessels and migration to lymph nodes are largely unknown. Here, we have investigated these events in an in vivo mouse Mycobacterium bovis bacillus Calmette‐Guérin vaccination model, ex vivo mouse dermal explants, and in vitro Transwell system comprising monolayers of primary human dermal lymphatic endothelial cells. We demonstrate that neutrophils are reliant on endothelial activation for adhesion, initially via E‐selectin and subsequently, by integrin‐mediated binding to ICAM‐1 and VCAM‐1, combined with CXCL8‐dependent chemotaxis. Moreover, we reveal that integrin‐mediated neutrophil adhesion plays a pivotal role in subsequent transmigration by focusing the action of matrix metalloproteinases and the 15‐lipoxygenase‐1‐derived chemorepellent 12( S )‐hydroxyeicosatetraenoic acid at neutrophil:endothelial contact sites to induce transient endothelial junctional retraction and rapid, selective neutrophil trafficking. These findings reveal an unexpectedly intimate collaboration between neutrophils and the lymphatic vessel endothelium, in which these phagocytic leukocytes act as pathfinders for their own transit during inflammation.